Role of cervical length evaluation with transvaginal ultrasound for prediction of preterm delivery in low risk pregnancy - Reddy, Sirupa Venkata Geetika; Mudanur, S. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm birth possess a major health burden to the society due to its long - term morbidity, perinatal mortality and high financial expenditures associated with it. Transvaginal ultrasonographic measurement is an effective and objective way of measuring the cervical length. Cervical length <25 mm is considered as the best cervical parameter with a good predictive accuracy for preterm birth. This study was taken up to study the role of cervical length measurement in predicting preterm labor by Trans vaginal sonography (TVS) and to measure cervical length and follow up cases to study the fetal outcome. Methods: Sagital long-axis view of endocervical canal along the entire length was obtained with high frequency endovaginal probe and the length of cervix from external to the internal os was measured. Atleast three measurements were obtained and the best shortest measurement in millimeters was recorded. Transfundal pressure was applied for 15 seconds and cervical length was obtained again. The cases are followed till delivery and outcome is noted. Results: Out of 134 study group of low risk women, 5.9% women and 50% of the women with short cervical length (<25 mm) had preterm birth. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of our study are 75%, 95.2%, 50%, 98.4%, 94% respectively. Among the 134 newborns, majority of the admissions (14) were due to birth asphyxia followed by meconium aspiration syndrome. Conclusions: TVS is a useful technique in assessing the cervical changes during pregnancy and predicting the preterm birth especially when performed between 16-24 weeks of gestational age could identify all the women having short cervical length along with other changes of cervix.